2018
DOI: 10.1186/s12993-018-0148-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social defeat stress on dopamine D2 receptor isoforms and proteins involved in intracellular trafficking

Abstract: BackgroundChronic social defeat stress induces depression and anxiety-like behaviors in rodents and also responsible for differentiating defeated animals into stress susceptible and resilient groups. The present study investigated the effects of social defeat stress on a variety of behavioral parameters like social behavior, spatial learning and memory and anxiety like behaviors. Additionally, the levels of various dopaminergic markers, including the long and short form of the D2 receptor, and total and phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 65 publications
0
21
1
Order By: Relevance
“…Both obesity and PS can separately generate anxiety [58,59]. Therefore, using the elevated plus maze (EPM) test specifically designed for this purpose [60], we next determined how effective obesity and PS are in triggering anxiety, when administered alone or in combination.…”
Section: Resultsmentioning
confidence: 99%
“…Both obesity and PS can separately generate anxiety [58,59]. Therefore, using the elevated plus maze (EPM) test specifically designed for this purpose [60], we next determined how effective obesity and PS are in triggering anxiety, when administered alone or in combination.…”
Section: Resultsmentioning
confidence: 99%
“…This reduction of the ISI in defeated mice has been associated with the social avoidance that characterizes affective disorders (Golden et al, 2011), and has been repeatedly observed after RSD or social instability (Krishnan et al, 2007;Golden et al, 2011;Henriques-Alves and Queiroz, 2016;Browne et al, 2018;Dong et al, 2018;Hodges et al, 2018). Furthermore, the ISI is the most used measure to distinguish between mice that are resilient or vulnerable to the effects of different models of social defeat (Krishnan et al, 2007;Chaudhury et al, 2013;Donahue et al, 2014;Friedman et al, 2014;Hodes et al, 2014;Isingrini et al, 2016;Sun et al, 2016;Nelson et al, 2018;Prabhu et al, 2018;Gururajan et al, 2019). In this line, we have also observed a subgroup of resilient mice (with similar ISI to that of control mice) and another subgroup of vulnerable mice that displayed social avoidance.…”
Section: Resilience To the Long-term Effects Of Rsd On Cocaine Cpp Ismentioning
confidence: 95%
“…The following tests were performed before and after SDS: novel object recognition test (NORT), open field test (OFT) and social interaction test (SIT). The detailed procedures were described in our previous studies [24,25,26].…”
Section: Methodsmentioning
confidence: 99%
“…Two isoforms of the D2R, D2L and D2S have been analyzed previously and a few modifications were observed [33,34]. A detailed description of this analysis was reported in our previous study [26]. Glutaraldehyde-treated membranes were incubated in 5% skimmed milk overnight at 4 °C with rabbit polyclonal antibodies against D2L (1:2000) and D2S (1:5000) (AbClon, Inc., Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%